Evaluation of the gastrointestinal anti-motility effect of Anacardium occidentale stem bark extract: A mechanistic study of antidiarrheal activity - Blessing O. Omolaso; Francis S. Oluwole; Olugbenga A. Odukanmi; Julius K. Adesanwo; Ahmed A. Ishola; Kayode E. Adewole (Elsevier, 2021)
Diarrhea is a prevalent gastrointestinal problem associated with fatal implications. It is a huge public health concern that requires better alternatives to current drugs. This study investigated the mechanisms involved in the antidiarrheal activity of Anacardium occidentale (Ao) stem bark extract, a plant commonly used in the management of diarrhea in Nigeria. Methanolic stem bark extract of the plant was partitioned into three fractions: hexane fraction, ethyl acetate fraction (AoEF) and methanol fraction. In vitro studies on the effect of these fractions on guinea pig ileum (GPI) strips, as well as the modulatory effect of AoEF on standard agonists- and antagonists-induced GPI contraction and relaxation, revealed AoEF as the most active fraction. In vivo studies to assess the effect of AoEF on the dopaminergic, muscarinic, and serotonergic pathways were carried out using gastric emptying (GE) and gastrointestinal transit (GT) as experimental end points. AoEF was subjected to GC-MS analysis, while the identified compounds were docked with the muscarinic acetylcholine receptor M3 (CHRM3) using AutodockVina. Results indicated that AoEF inhibited GE and GT via inhibition of CHRM3. In addition, GC-MS analysis revealed the presence of 24 compounds in AoEF, while docking indicated that octadecanoic acid 2-(2-hydroxylethoxy) ethyl ester exhibited the highest binding affinity to CHRM3. This study indicated that the antidiarrheal activity of Ao is through its antimotility effect via the inhibition of the muscarinic pathway. And since none of the identified compounds exhibited higher binding affinity to CHRM3 relative to loperamide, the antimotility activity of these phytoconstituents may be via synergism.